The DBS Handbook Of Geomorphology - Aijaz, Sabera (New Delhi: Dbs Imprints, 2018)
Geomorphology is the scientific study of the origin and evolution of topographic and bathymetric features, created by physical, chemical, or biological processes, operating at or near the Earth$1 (Bs surface. Geomorphologists seek to understand, why landscapes look the way they do, to understand landform history and dynamics and to predict changes, through a combination of field observations, physical experiments and numerical modelling. Geomorphology is the study of landforms, their processes, form and sediments, at the surface of the Earth (and sometimes on other planets). Study includes looking at landscapes to work out, how the earth surface processes, such as air, water and ice, can mould the landscape.s
Includes Bibliography and index
Keywords: Geomorphology; Landforms; Physical geography; Geological processes